Functionalization of Adhesive Bonding to Control On-Demand Disassembly of Composite Aeronautical Structures - Lorraine Aparecida Silva; Christine Espinosa; Rémy Chieragatti; Eric Paroissien; Frédéric Lachaud; Lucas Filipe Martins da Silva (Aerospace)
In the context of enhancing the sustainability of aerospace vehicles, the structures must be designed to anticipate the possibility of disassembly. Mandatory certification in aeronautics and the robustness of satellites require structures to maintain their integrity to ensure safety during their life, which can come into conflict with the need for disassembling or demising. This is particularly the case for composite structures assembled though adhesive bonding. In this paper, a controlled disassembly device of the substrates of a component for keeping their integrity and surface states after debonding is proposed. The addition of thermally expandable particles (TEPs) and a metallic grid is investigated in various proportions, substrates, and adhesives. It is shown that the introduction of the disassembling system into a 100 µm adhesive bonding does not significantly affect the strength of the joint during life. Disassembly only happens when and if desired at a load level above the natural mode I and mode II ruptures of the assembly. The proposed solution helps to make functionalization of the bonded joint a good way to address sustainability regarding the preservation of resources, transforming the adhesive joint into a structural functional material.